Online learning during the pandemic of COVID-19: Experiences of students and universities - Savić, Ilija; Alčaković, Slavko (The European Journal of Applied Economics, 2022)
The COVID-19 pandemic had a significant influence on university education and organization of lecturing. Most universities throughout the world had not been prepared for the new circumstances, and this ultimately affected both the organization and the quality of lectures. Universities were obliged to follow trends and implement new strategies in lecturing in order to support their students where help was most required, and furthermore, in order to maintain the quality of their experiences and education. The objective of this research was to gain insight into how students reacted to the new pandemic situation and whether they are satisfied with online teaching so that universities could use the results to adapt and conduct online teaching in the future. The research found that students considered online learning had affected their efficiency, productivity, and level of motivation in the process of learning. Apart from these adversities regarding online teaching and learning, the survey found that the students’ attitude toward the implementation of technology in university education would improve the process of online lecturing and examination and enhance the present situation.